Pengaruh Pembelajaran Daring Terhadap Minat Belajar Siswa Pada Mata Pelajaran Pendidikan Kewarganegaraan Kelas IV Dan V SD - Nasaruddin Nasaruddin; rohana rohana; muhammad irfan; achmad achmad (Universtas Negeri Makassar, 2022)
This study aims to determine the effect of online learning on students' interest in learning in civic education subjects for class IV and V at SDN Samata, Somba Opu District, Gowa Regency. This research is an expost facto quantitative research that shows the effect of variable X on variable Y. The results showed that the influence of online learning variables on students' reading interest at SDN Samata, Somba Opu District, Gowa Regency was in the medium category. Meanwhile, based on the results of data analysis, it shows that there is a positive and significant influence between online learning on student interest in learning at SDN Samata District, Soma Opu District, Gowa Regency. This can be seen from the results of research on online learning and learning interest so that the influence of online learning on student learning interest in Civics Education Subjects Class IV and V SDN Samata, Somba Opu District, Gowa Regency can be accepted.